Finding a Way Home - Mwanaka, Tendai R. (Book collections on Project MUSE., 2015)
Home is a place in ourselves where we are happy with ourselves, where we find peace with ourselves, where we are satisfied, fulfilled... The important theme coursing through all the stories in the novel, Finding a way home, is that we have to make the journey to find our homes, we have to find the path, and start walking in that path.